Leading diversity in the 21st century - Scandura, Terri A.; Mouriño-Ruiz, Edwin (Emerald Publishing Limited : IAP -- Information Age Publishing, Inc., 2017)
The Leader-Member Exchange (LMX) model of leadership has shown that effective leader-follower relationships predict employee well-being and performance. Less research, however, addressed how diversity variables may affect the development of leader-member exchange and outcomes. This book moves the field forward by addressing the 21st century challenges of how diversity may impact the development of effective working relationships.Key trends in the workforce suggest that the impact of diverse employees will challenge a leader's ability to develop effective working relationships with all direct reports. New frameworks are needed to understand how various groups such as women, Hispanics, African Americans, Millennials, LGBTQ, and persons with Autism Spectrum Disorder develop effective working relationships with their supervisors This edited volume will bring together the top scholars in the field to address these segments of the workforce and offer practical advice for managers.This book will be used in college undergraduate and/or graduate level leadership classes. It might also be adopted for courses in managing diversity. Scholars will find the book a useful reference work. In addition, practicing managers will be interested in the implications of developing effective working relationships in diverse leader-member dyads.
Keywords: Diversity in the workplace.; Personnel management.; Communication in management.; Leadership.; Business & Economics -- Diversity & Inclusion.; Diversity, equality and inclusion in the workplace.; elektronické knihy; electronic books